J. Fitz, The Great Age of Pannonia (A. D. 193–284), Corvina Kiado, Budapest 1982, pp. 80, 105 illustrations, 21 drawings and maps - Żyromski, Marek (Balcanica Posnaniensia. Acta et studia, 1990)
Żyromski Marek, book review: J. Fitz, The Great Age of Pannonia (A. D. 193–284), Corvina Kiado, Budapest 1982, ss. 80, 105 il. oraz 21 rysunków i map, „Balcanica Posnaniensia. Acta et Studia” 1990, t. 5, s. 440.